2023
DOI: 10.1108/pm-07-2022-0052
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of facilities management sourcing approaches in hotels in Ghana: a study of selected hotels in Wa

Abstract: PurposeThe study aims to assess the sourcing approaches used in providing facilities management (FM) services in hotels. It further explores the factors that influence hotels' choice of sourcing approach and the challenges.Design/methodology/approachThe study used a case study design. Simple random, census and purposive sampling techniques were used to select the hotels and respondents. Data were collected using interviews and analysed thematically. The data were presented in narration and direct quotes from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 70 publications
(193 reference statements)
0
14
0
Order By: Relevance
“…This was attributed to capacity and funding challenges, as well as the need to focus on their core activities. These issues have been identified as major factors influencing the sourcing of FM services in hotels (Tannor et al, 2022;Alhassan et al, 2023). A hotel manager recounted: Another hotel manager added:…”
Section: The Existence Of Facilities Management Units In Hotelsmentioning
confidence: 99%
See 2 more Smart Citations
“…This was attributed to capacity and funding challenges, as well as the need to focus on their core activities. These issues have been identified as major factors influencing the sourcing of FM services in hotels (Tannor et al, 2022;Alhassan et al, 2023). A hotel manager recounted: Another hotel manager added:…”
Section: The Existence Of Facilities Management Units In Hotelsmentioning
confidence: 99%
“…Studies on FM in hotels have identified maintenance, cleaning, security and information technology services as the key FM services (Nora and Blakstad, 2016; Ramanathan, 2012; Li et al , 2013; Park et al , 2019; Ghazi, 2016; Alhassan et al , 2023). Rasmussen et al (2019) concluded that, delivering comfortable workplaces with quality services has become a major necessity for FM.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…FM in buildings embodies operating, maintaining, improving and adapting the building and its services to create an environment that strongly supports the goal of an institution (Atkin and Brooks, 2015). FM can be done in-house where FM activities are done by staff and resources of the organisation itself (Atkin and Brooks, 2015), or it can be outsourced to a specialist third-party service provider at a fee (Alhassan et al , 2023; Amos and Gadzekpo, 2016; Tannor et al , 2022a). A hybrid FM strategy can combine both approaches by providing certain services in-house while outsourcing the rest to a third-party (Atkin and Brooks, 2015; Moreira et al , 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In the outsourcing FM strategy, the FM function is contracted to a third-party vendor who charges a fee for delivering such services (Alhassan et al , 2023; Hiamey and Hiamey, 2019; Amos and Gadzekpo, 2016a, 2016b). This creates a principal–agent relationship between the property owner and FM service provider in which the agent receives some fees for the services (Tannor et al , 2022b).…”
Section: Introductionmentioning
confidence: 99%